2023
DOI: 10.3390/vaccines11020489
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between COVID-19 Infection and Kidney Diseases: A Review on the Metabolomic Approaches

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19, a respiratory disorder. Various organ injuries have been reported in response to this virus, including kidney injury and, in particular, kidney tubular injury. It has been discovered that infection with the virus does not only cause new kidney disease but also increases treatment difficulty and mortality rates in people with kidney diseases. In individuals hospitalized with COVID-19, urinary metabolites from several metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 231 publications
(254 reference statements)
0
4
0
Order By: Relevance
“…Technologies and computing instruments allow for a more detailed and comprehensive exploration of many metabolites in a single assessment, offering a wider perspective on disease mechanisms. Metabolomics has allowed the detailed investigation of kidney diseases by assessing related molecular pathways and has initiated the development of novel molecular diagnostic tools for nephrology [94,95].…”
Section: Kidney Diseasementioning
confidence: 99%
“…Technologies and computing instruments allow for a more detailed and comprehensive exploration of many metabolites in a single assessment, offering a wider perspective on disease mechanisms. Metabolomics has allowed the detailed investigation of kidney diseases by assessing related molecular pathways and has initiated the development of novel molecular diagnostic tools for nephrology [94,95].…”
Section: Kidney Diseasementioning
confidence: 99%
“…A meta-analysis ( 8 ) found that 4.5% of all confirmed COVID-19 cases develop AKI, mostly prevalent in critical COVID-19 cases. More recent studies report the incidence of AKI to be 15%–25% and is specifically high in COVID-19 patients with pre-existing complications ( 9 ). Due to the high incidence of kidney damage during COVID-19, understanding precisely how SARS-CoV-2 affects the kidney during COVID-19 can help improve treatment of patients during hospitalization, as well as improve recovery of long-term COVID-19 or post-COVID-19 patients suffering from kidney complications.…”
Section: Introductionmentioning
confidence: 99%
“…As for the origin of AKI during COVID-19, many causal factors have been proposed, including hyper-coagulation, microangiopathy, rhabdomyolysis, endothelial activation, dysregulation of complement, and angiotensin-converting enzyme 2 (ACE2) pathway activation ( 9 , 10 ). In addition, the direct cytotoxic effect of viral infection has also been suggested as a cause of kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic profiling can complement the lack of knowledge regarding the molecular mechanisms underlying clinical manifestations and pathogenesis of COVID-19. Consequently, several studies have employed metabolomic approaches to better understand the metabolic pathways involved in COVID-19 pathogenesis ( Ansone et al, 2021 ; Chen et al, 2022 ; Murali et al, 2023 ). Serum-based metabolomic studies in COVID-19 patients revealed altered glycolytic pathways as well as amino acid, lipid, and anaplerotic metabolism, suggesting an impact on energy pathways, inflammatory response, and oxidative stress, and confirming the systemic nature of the disease ( Kimhofer et al, 2020 ; Lorente et al, 2021 ; Shi et al, 2021 ; Valdés et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%